Peningkatan Daya Saing Sumber Daya Manusia Dalam Menghadapi Revolusi Industri 4.0 - Setiono, Beni Agus (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2019)
This article intends to examine the Increased Competitiveness of Human Resources in Facing the Industrial Revolution 4.0. The formulation of the problem is: 1). What should the Indonesian government do in preparing for the industrial revolution 4.0? 2). What will happen if the two things are not done? 3). How is Indonesia step in dealing with Industry 4.0? The data analysis method of the study was conducted using descriptive, analytic and qualitative methods which were supplemented by literature studies and observations of existing practices. This study concludes that Indonesia is improving itself in preparing for the industrial revolution 4.0 where there will be many changes, including employment. Future challenges will occur large-scale automation, where between computers can communicate with each other through a cloud server. New jobs in the past will emerge in this industrial era.